Prosthetisation of a K2 Patient with Sub-ischial Socket Compared to Ischial Containment (IC) Socket: A Case Report - Buratti, Davide; Vaccari, Matteo (Poltekkes Kemenkes Jakarta I, 2025)
Background: Ischial Containment Socket (ICS) has been the standard treatment for transfemoral amputees for thirty years, but the high edges and the ischial containment contribute to the discomfort of the socket especially when the patient is standing and while he is sitting.Aims: The purpose of this study is to compare ICS to sub-ischial socket in a unilateral TFA K2 patient.Methods: Two custom-fabricated sockets, worn full-time for 3 weeks, with testing on day 0 and at 3 weeks after socket delivery. The case report examined a 71-year-old woman three years after one-sided transfemoral amputation to the right leg, with K2 functional level. The protocol used contained three questionnaires, the measurement of the hip range of motion and 2 physical tests.Results: The most relevant results were the reduction of the pelvic inclination during the sitting with a variation of -42.9% (7° with the ICS and 4° with the sub-ischial socket), and an increase in all the measurements of the angles of the hip, especially in abduction and extension with percentage change that reaches +300% each. The two sockets were equivalent in the 2MWT (P-value=0.98) and in the 4SST (P-value=0.88) (statistical significance p<0.05). The patient reported that the sub-ischiatic socket is more comfortable and has more freedom of movement.Conclusion: It can be said that for patient K2 examined, the sub-ischial socket is a valid clinical alternative to the one with ischial containment, since it does not affect aspects such as stability and dynamics, but it also offers improvements in the stump-socket interface.